Evaluasi Pelaksanaan Program Wirausaha Merdeka Politeknik Kutaraja Tahun 2023 - Aini, Zahriatul; Puspita, Desy; Agustina; Mirnawati; Rahman, Abdul (Jurnal EMT KITA, 2024)
The aim of this research is to evaluate the success of the Independent Entrepreneurship program implemented by the Kutaraja Polytechnic Independent Entrepreneurship team. The aspect assessed is satisfaction with the implementation of the Independent Entrepreneurship program by students, field assistant lecturers and MSME mentors. This research uses a qualitative approach with descriptive methods. The respondents of this research were students participating in the Merdeka Polytechnic Entrepreneurship Kutaraja, field assistant lecturers in the Merdeka Polytechnic Entrepreneurship Kutaraja and MSME partners of the Independent Entrepreneurship Kutaraja Polytechnic. Data from the questionnaire results were obtained through the implementation team of the Kutaraja Polytechnic Independent Entrepreneurship program. The results of this research were that 41.78% of students, field assistant lecturers and MSME mentors were very satisfied with the implementation of Independent Entrepreneurship carried out by the Kutaraja Polytechnic Independent Entrepreneurship team.